2022
DOI: 10.1039/d1sc06268a
|View full text |Cite
|
Sign up to set email alerts
|

In-solution direct oxidative coupling for the integration of sulfur/selenium into DNA-encoded chemical libraries

Abstract: Sulfur/selenium-containing electron-rich arenes (ERAs) exist in a wide range of both approved and investigational drugs with diverse pharmacological activities. These unique chemical structures and bioactive properties, if combined with the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…This indicated that our on-DNA vinyl sulfones could be potentially used in DNA–protein conjugate labelling. 30 Moreover, the sulfide in the thiol adduct product aa36 could be further converted into the corresponding sulfoxide through our previously reported protocol, 31 as shown in Scheme 5b. This chemical transformation provided additional diversification, conceptually in accordance with the DEL technology.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that our on-DNA vinyl sulfones could be potentially used in DNA–protein conjugate labelling. 30 Moreover, the sulfide in the thiol adduct product aa36 could be further converted into the corresponding sulfoxide through our previously reported protocol, 31 as shown in Scheme 5b. This chemical transformation provided additional diversification, conceptually in accordance with the DEL technology.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, this reaction provides a unique solution to increase the reactivity of highly diluted DNA‐conjugated substrates and abolishes the need of heavy metals from photocatalysts. Recently, Li and coworkers reported an in‐solution oxidative coupling procedure that could efficiently incorporate Se into DNA‐conjugated electron rich arene (ERA) under mild conditions (Figure 3iic) [35] . This method features a transition‐metal free process and a broad scope of Se source, including diselenide, selenol, selenyl chloride, sulfonyl selenol and Ebselen.…”
Section: Dna Compatible Reaction Development For the Synthesis Of Sedelmentioning
confidence: 99%
“…Recently, Li and coworkers reported an in-solution oxidative coupling procedure that could efficiently incorporate Se into DNA-conjugated electron rich arene (ERA) under mild conditions (Figure 3iic). [35] This method features a transition-metal free process and a broad scope of Se source, including diselenide, selenol, selenyl chloride, sulfonyl selenol and Ebselen.…”
Section: Dna Compatible Reaction Development For the Synthesis Of Sedelmentioning
confidence: 99%
“…To expand the chemical space of these DNA-Encoded Libraries, a greater variety of DNA-Compatible reactions is required. Although much progress has been made in this direction ( Potowski et al, 2021 ; Nie et al, 2022 ; Shen et al, 2022 ; Yang et al, 2022 ), the availability of efficient synthetic methods for the synthesis of DELs remains an important challenge.…”
Section: Introductionmentioning
confidence: 99%